1. ## Vector proof

Given that three vectors $\vec a, \vec b, \vec c$, are perpendicular to each other (where $\vec a, \vec b, \vec c$ are not $\vec 0$ and given that $p\vec a+q\vec b+r\vec c=\vec 0$, show that p=q=r=0.

I get the solution, but I don't understand something written in my solution book.

It says

Since $p\vec a+q\vec b+r\vec c=\vec 0$

$\vec a(p\vec a+q\vec b+r\vec c)=0$

Notice that in the second line it is just 0, not $\vec 0$

Why?

2. Originally Posted by chengbin
Given that three vectors $\vec a, \vec b, \vec c$, are perpendicular to each other (where $\vec a, \vec b, \vec c$ are not $\vec 0$ and given that $p\vec a+q\vec b+r\vec c=\vec 0$, show that p=q=r=0.

I get the solution, but I don't understand something written in my solution book.

It says

Since $p\vec a+q\vec b+r\vec c=\vec 0$ <<<<< the result is the null vector which is perpendicular to any other vector

$\vec a(p\vec a+q\vec b+r\vec c)=0$ <<<<<< since the null vector is perpendicular to any other vector the scalar (dot) product must be zero. (A dot product yields a real number not a vector!)

Notice that in the second line it is just 0, not $\vec 0$

Why?
...

3. ## Scalar Product

Hello chengbin
Originally Posted by chengbin
Given that three vectors $\vec a, \vec b, \vec c$, are perpendicular to each other (where $\vec a, \vec b, \vec c$ are not $\vec 0$ and given that $p\vec a+q\vec b+r\vec c=\vec 0$, show that p=q=r=0.

I get the solution, but I don't understand something written in my solution book.

It says

Since $p\vec a+q\vec b+r\vec c=\vec 0$

$\vec a(p\vec a+q\vec b+r\vec c)=0$

Notice that in the second line it is just 0, not $\vec 0$

Why?
$\vec a(p\vec a+q\vec b+r\vec c)$ is the scalar or dot product of the vector $\vec a$ with the vector $p\vec a+q\vec b+r\vec c$, and is more correctly written $\vec a.(p\vec a+q\vec b+r\vec c)$

Since the vector $(p\vec a+q\vec b+r\vec c) = \vec 0$, this scalar product is the scalar 0.

The proof then (presumably) continues by noting that $\vec a.\vec b = 0 = \vec a . \vec c$, since the scalar product of perpendicular vectors is zero.

Hence $p \vec a.\vec a = 0$, and hence (if $\vec a$ is a non-zero vector) $p = 0$.

Similarly q = r = 0.